Getting time and building trust: unveiling the systemic, relational, and personal factors influencing clinical pharmacy service implementation in South Africa, a qualitative study - Lucille Crafford; Rashmi A Kusurkar; Elmien Bronkhorst; Andries Gous; Anouk Wouters (BMC Medical Education)
Abstract Background While multidisciplinary teams with clinical pharmacists improve medication use and outcomes, their integration in South Africa faces limitations. A lack of dedicated positions and healthcare professionals’ misunderstanding restrict ward activities and hinder full collaboration, limiting their potential to optimize patient care. This study addresses a gap by exploring how perceived healthcare professionals’ understanding of clinical pharmacists’ roles impacts their motivation and service implementation. Understanding these dynamics, particularly in resource-constrained settings, is crucial for optimizing integration and healthcare delivery. Methods Adopting a constructivist approach, this qualitative study was conducted using focus group discussions. Through purposive sampling clinical pharmacists were recruited across South Africa’s public healthcare sector. A semi-structured guide based on previous findings explored how the perceived understanding around clinical pharmacy impacts service delivery and work motivation. Transcripts were analyzed using thematic analysis, guided by the Self-Determination Theory framework. Thematic analysis employed an inductive approach, following an initial preliminary analysis of open and selective coding to develop a coding framework. Results Clinical pharmacists (n = 16) reported various challenges impacting service implementation and motivation. Two main themes were identified: (1) Time: Dedicated ward time is crucial for both the proper implementation of clinical services, as well as the clinical pharmacists’ motivation; and (2) Trust: Clinical pharmacists experience a lack of trust amongst healthcare professionals in the value of clinical pharmacy services. The themes illustrated mechanisms at work at three levels: systemic (lack of dedicated positions), inter-relational (healthcare professional’s misconceptions), and personal (thwarted autonomy). Conclusions Systemic challenges, like the absence of official positions present the biggest obstacle, affecting support, scope of practice, and healthcare professional interactions. While systemic changes are crucial for full integration of clinical pharmacists, in resource-constrained settings fostering autonomous motivation is equally important. This study emphasizes the need for a multi-faceted approach, including policy changes, international collaboration, interprofessional education, and interventions to empower clinical pharmacists for proactive service delivery. By addressing these interconnected challenges, healthcare systems can leverage the full potential of clinical pharmacists, ultimately improving healthcare delivery and patient outcomes.